Energy Efficiency in Wireless Networks (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint features 18 selected high-quality research articles spanning diverse domains in the field of energy-efficient wireless communication and networking. The contributions in this reprint collectively underscore the significance of energy optimization in wireless systems, illuminating innovative approaches, algorithms, and technologies that pave the way for sustainable and efficient wireless communication in various application scenarios. This reprint brings together a rich tapestry of research that illuminates the ongoing efforts to design, optimize, and implement energy-efficient wireless communication and networking solutions. This reprint also encourages researchers to explore finer areas in the energy-efficient wireless network domain and provides a significant contribution to the research community to help further extend their areas of research.